Stress testing at the Magyar Nemzeti Bank - Ádám Banai; Zsuzsanna Hosszú; Gyöngyi Körmendi; Sándor Sóvágó; Róbert Szegedi (Magyar Nemzeti Bank, 2014)
Our study presents the top-down stress testing framework currently used by the Magyar Nemzeti Bank. We run separate solvency and liquidity stress tests to analyse the ability of the banking system to absorb shocks and we present their results in our Report on Financial Stability. In the former, we focus mostly on credit risk but also take into account losses due to market risks. Our study explains in detail the method we apply to quantify the impact of a negative two-year macroeconomic shock on the capital adequacy ratio. We explain the models we use for calculating profit before loan losses, PDs and LGD. We also demonstrate how we measure the impact of an intensive 30-day liquidity shock on the banking system. Finally, we use the stress test completed in the spring of 2013 to explain in detail how the results should be interpreted and what conclusions we can draw from them.
Keywords: E44; E47; G21; 330; stress test; liquidity risk; credit risk